2003
DOI: 10.1007/bf03402102
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 Deficiency Increases Atherosclerosis, Thrombosis, and Low-density Lipoproteins in Apolipoprotein E Knockout Mice

Abstract: Interleukin (IL)-10 is an anti-inflammatory cytokine that may play a protective role in atherosclerosis. The aim of this study was to assess the effect of IL-10 deficiency in the apolipoprotein E knockout mouse. Apolipoprotein E deficient (E-/-) and IL-10 deficient (-/-) mice were crossed to generate E-/ϫ IL-10-/double knockout mice. By 16 wk, cholesterol and triglycerides were similar in double and single knockouts but the lack of IL-10 led to increased low-density lipoprotein cholesterol whereas very-low-den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
204
0
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 297 publications
(226 citation statements)
references
References 53 publications
17
204
0
5
Order By: Relevance
“…Increased concentration of TGF-β and IL-10 was associated with suppressing pathogenic inflammatory responses, regulating immunity and promoting atherosclerotic plaque stabilization (33). On the contrary, deletion of TGF-β or IL-10 signaling accelerates atherosclerosis and plaque vulnerability (34,35). In the present study, mRNA and protein levels of TGF-β and IL-10 were significantly increased in atherosclerotic plaques in ApoE -/-mice after 6 wks of simvastatin treatment.…”
Section: Tregs Are a Unique Subset Of T Cells Although The Number Ofsupporting
confidence: 40%
“…Increased concentration of TGF-β and IL-10 was associated with suppressing pathogenic inflammatory responses, regulating immunity and promoting atherosclerotic plaque stabilization (33). On the contrary, deletion of TGF-β or IL-10 signaling accelerates atherosclerosis and plaque vulnerability (34,35). In the present study, mRNA and protein levels of TGF-β and IL-10 were significantly increased in atherosclerotic plaques in ApoE -/-mice after 6 wks of simvastatin treatment.…”
Section: Tregs Are a Unique Subset Of T Cells Although The Number Ofsupporting
confidence: 40%
“…The effect of IL-10 on atherogenesis has been studied extensively with different mouse models, all of which demonstrated that IL-10 is an antiatherogenic factor (29)(30)(31). Accordingly, the raised IL-10 plasma levels in A20-haploinsufficient mice may also protect against lesion formation.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-inflammatory cytokine IL-10 generates protective signals against atherosclerosis shown in IL-10 deficient mice by increased and in IL-10 transgenic mice by decreased lesion formation [136][137][138]. 15d-PGJ 2 can inhibit IL-10 signaling in a STAT3 dependent and PPAR-c-independent way [139].…”
Section: Inflammatory Cytokines: Agitators Of Inflammatory Milieumentioning
confidence: 99%